UMPSA Quality and Innovation Day 2025 strengthens culture of excellence and innovation at workplace - Naqiah, Puaad (UMPSA, 2025)
PEKAN, 13 June 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) continues to strengthen the culture of excellence and innovation among its community through the organisation of the Quality and Innovation Day (HKI) 2025 held at the Multipurpose Hall, UMPSA Pekan.